The management of the learning content - Lasić-Lazić, Jadranka (Array, 2004)
Although knowledge has always been important, today, due to the world market globalisation and with such strong competition, it is becoming the most important element in the production of goods. Knowledge has become so important, that we can easily say that in this Information Age goods are in themselves the products of knowledge. Therefore, if knowledge is the principal resource, if it is the very essence of the values through work materialized into produced goods, then the successful management of modern production is only possible if its basic resource - knowledge - is also effectively managed. Taking into consideration these changing conditions, the authors of this paper deal particularly with textbooks and other educational materials suggesting how easily and promptly make them dynamic, reusable, interactive, scalable, and flexible.